Unionism and the Cyclical Behavior of the Labor Market in U.S. Manufacturing - Pearce, James E. (The Review of Economics and Statistics, 1983)
T HE traditional view of market dynamics implies that when demand varies, intertemporal variation in quantities exchanged increases as prices become less flexible. This reasoning leads to the proposition that wage and price rigidities are important contributors to cyclical fluctuations in output. Fischer (1977a) and Gray (1978) based formal macro models on this principle. Although this view is common, it has little empirical support.' The coexistence of union and nonunion establishments engaged in similar activities contains potential for testing its merits. Economists have long maintained that in the short run, union wages are less flexible than nonunion wages (Dunlop (1950), Rees (1951)). This difference should produce larger fluctuations in union employment and hours. Empirical studies have generally supported the union wage rigidity hypothesis (Lewis (1963), Ashenfelter, Johnson, and Pencavel (1972), and Hendricks (1981)),2 but until recently, lack of data precluded analysis of hours and employment. Definitive answers to the important questions concerning unions' influence on cyclical behavior require yet unavailable information matching the behavior of firms and characteristics of workers, but data from modem surveys have allowed considerable progress. Nevertheless, it remains a challenge to determine how much of differences observed in the stability of labor utilization are attributable to differences in the stability of demand. Medoff (1979) and Raisian (1979) report that cyclical variation of employment and hours is indeed greater for union labor. But despite attempts to allay suspicion that their finding arises primarily from concentration of union members in cyclically sensitive industries, both studies leave room for doubt. Raisian estimated functions relating an individual's wage and weeks worked in a year to a proxy for excess demand (that year's unemployment rate) in the worker's industry. The technique is attractive, but Raisian's data included workers from the entire economy, and the industries were broad aggregates. Thus, differences in the union and nonunion groups' compositions may play a large role. Medoff, who confined his study to production workers in manufacturing and used data allowing finer partitions, investigated the importance of composition more thoroughly. But he did not estimate relationships between adjustments in employment or hours and a measure of demand. Furthermore, his focus was principally on the composition of manhours adjustments rather than their size. In this paper I combine the strongest features of the Medoff and Raisian studies in further examination of the influence of unionism on cyclical fluctuations. Using Current Population Surveys (U.S. Department of Commerce (1978)) from May of 1973-75, my analysis covers production workers in manufacturing during a period of rising inflation and unemployment. The heart of the analysis is a measure of residual employment that quantifies, by three-digit industry and year, shortrun excess demand for labor. I construct this variable from employment time series and use it to estimate union-nonunion differences in the cyclical responses of unemployment, hourly wage rates, and hours worked. The results are consistent with the view that increasing rigidity in wages amplifies cyclical fluctuations in the utilization of labor. The wage regressions add further to the literature's already strong support for the union wage rigidity hypothesis. The employment status and hours regressions imply that the sensitivities of employment Received for publication August 12, 1981. Revision accepted for publication February 11, 1983. * Federal Reserve Bank of Dallas. This paper is based on my Ph.D. dissertation, which was completed at UCLA with financial assistance from the Rand Corporation and the Department of Labor. Comments by referees and by participants of labor workshops at UCLA and the University of Chicago, as well as the computation assistance of Brian McKee, are gratefully acknowledged. I am responsible for any remaining errors. The views expressed should not be attributed to the Federal Reserve Bank of Dallas or the Federal Reserve System. ' One study is Gordon (1982), who concludes (page 41) that, macroeconomic instability in the United States has been aggravated by the unusually sluggish behavior of nominal wages in the postwar era. 2See also Johnson (1975), Parsley (1980), and Moore and Raisian (1980).